Short Communication: Contamination of cell phones by pathogenic microorganisms: Comparison between hospital staff and college students - PURNIMA R. CHITLANGE (Nusantara Bioscience, 2014)
Abstract. Chitlange PR. 2014. Contamination of cell phones by pathogenic microorganisms: Comparison between hospital staff and college students. Nusantara Bioscience 6: 203-206. Cell phone (CP) is a long range portable electronic device. The cell phone is constantly exposed to arrays of microorganisms, making it a harbor and breeding ground for microbes especially those associated with skin. The adult human is covered with approximately 2m2 of skin with area supporting about 106 bacteria. To check whether the cell phone act as a vector for transmission of various pathogens, a potential study was carried out in Microbiology Department of Shri Radhakisan Laxminarayan Toshniwal College of Science, Akola, Maharashtra, India. Total of 20 cell samples was screened. Two parameters were considered: College students and hospital staff. The isolated bacteria Staphylococcus aureus, Escherichia coli, Pseudomonas sp., Bacillus subtilis, Aerobacter aerogenes, Salmonella, Shigella, Streptococci, P. vulgaris were identified on the basis of morphological and cultural characteristics. The main aim of present study was to check the contamination by bacterial pathogens on cell phones and also to check role of cell phone for transmission of pathogens from person to person or not.